Resource requirements for cancer registration in areas with limited resources: Analysis of cost data from four low- and middle-income countries. (December 2016) - Tangka, Florence K.L.; Subramanian, Sujha; Edwards, Patrick; Cole-Beebe, Maggie; Parkin, D. Maxwell; Bray, Freddie; Joseph, Rachael; Mery, Les; Saraiya, Mona; ,
Highlights: Host institution resources are crucial for registry operations and sustainability. Cancer registration involves substantial fixed costs and labor. Cost per inhabitant was smaller among registries serving large populations. Cost per case was smaller among lower income countries. Approaches to increase efficiency could serve to reduce registry costs. Abstract: Background: The key aims of this study were to identify sources of support for cancer registry activities, to quantify resource use and estimate costs to operate registries in low- and middle-income countries (LMIC) at different stages of development across three continents. Methods: Using the Centers for Disease Control and Prevention's (CDC's) International Registry Costing Tool ( IntRegCosting Tool), cost and resource use data were collected from eight population-based cancer registries, including one in a low-income country (Uganda [Kampala)]), two in lower to middle-income countries (Kenya [Nairobi] and India [Mumbai]), and five in an upper to middle-income country (Colombia [Pasto, Barranquilla, Bucaramanga, Manizales and Cali cancer registries]). Results: Host institution contributions accounted for 30%–70% of total investment in cancer registry activities. Cancer registration involves substantial fixed cost and labor. Labor accounts for more than 50% of all expenditures across all registries. The cost per cancer case registered in low-income and lower-middle-income countries ranged from US 3.77 to US 15.62 (United States dollars). In Colombia, an upper to middle-income country, the cost per case registered ranged from US 41.28 to US 113.39. Registries serving large populations (over 15 million inhabitants) had a lower cost per inhabitant (less than US 0.01 in Mumbai, India) than registries serving small populations (under 500, 000 inhabitants) [US 0.22] in Pasto, Colombia. Conclusion: This study estimates the total cost and resources used for cancer registration across several countries in the limited-resource setting, and provides cancer registration stakeholders and registries with opportunities to identify cost savings and efficiency improvements. Our results suggest that cancer registration involve substantial fixed costs and labor, and that partnership with other institutions is critical for the operation and sustainability of cancer registries in limited resource settings. Although we included registries from a variety of limited-resource areas, information from eight registries in four countries may not be large enough to capture all the potential differences among the registries in limited-resource settings.